The Effectiveness of Children YouTube Songs and Flashcard Games to Teach Vocabulary to Kindergarten Pupils - Widhiprasetya, Gabriella Anindyarizki; Mujiyanto, Januarius; Sutopo, Djoko (Universitas Negeri Semarang, 2021)
Teaching English to young learners has attracted many people in the last decades worldwide, so that English has been increasingly practised at the kindergarten levels. The role of parents is very crucial in the early stage of a child. This research shows the effective interaction between kindergarten children’s YouTube songs, flashcard games, and parental involvement in vocabulary learning at Kindergarten Karangturi with online teaching. This research was a quasi-experimental study with a 2x2 factorial design that focuses on two or more independent variables or factors on at least one dependent variable. This study employed two independent variables: teaching with YouTube songs and flashcard games based on the design. This study reveals that there was no significant interaction between two teaching media in teaching vocabulary and parent’s involvement. Using YouTube songs and flashcard games as the vocabulary teaching media to pupils with high parent involvement was effective. However, it also reveals that using youtube songs and flashcard games was ineffective as the vocabulary teaching media to pupils with low parent involvement. This study shows no significant difference in teaching vocabulary with YouTube songs compared with flashcard games to Karangturi Kindergarten pupils. Further research was expected to continue this study by finding another method to teach young learners English to enhance their language mastery.